RP-HPLC Determination of Atomoxetine Hydrochloride in Bulk and Pharmaceutical Formulations - H. R. Prajapati; P. N. Raveshiya; J. M. Prajapati (E-Journal of Chemistry)
A reversed phase high performance liquid chromatographic (RP–HPLC) method was developed and subsequently validated for the determination of atomoxetine hydrochloride in bulk and pharmaceutical formulation. The separation was done by a PerkinElmer Brownlee analytical C8 column (260 mm x 4.6 mm, 5 µm) using methanol: 50 mM KH2PO2 buffer (PH adjusted to 6.8 with 0.1 M NaOH), 80:20 v/v as an eluent. UV detection was performed at 270 nm at a flow rate 1.0 mL/min. The validation of the method was performed, and specificity, reproducibility, precision accuracy and ruggedness were confirmed. The correlation coefficient was found to be 0.997 for atomoxetine hydrochloride. The recovery was in the range of 99.94 to 100.98% and limit of quantification was found to be 5.707 µg/mL. The method is simple, rapid, selective and economical too and can be used for the routine analysis of drug in pharmaceutical formulations.